Probabilistic forecasting of ionospheric scintillation and GNSS receiver signal tracking performance at high latitudes - Paul Prikryl; Veettil Sreeja; Marcio Aquino; Periyadan T. Jayachandran (Annals of Geophysics, 2013)
At high latitudes, phase scintillation occurs predominantly on the dayside in the ionospheric footprint of the magnetospheric cusp, and in the nightside auroral oval. A new technique of probabilistic forecasting of phase scintillation occurrence relative to the arrival time of high-speed solar wind from coronal holes and interplanetary coronal mass ejections has recently been proposed [Prikryl et al. 2012]. Cumulative probability distribution functions for the phase-scintillation occurrence that are obtained can be specified for low (below-median) and high (above-median) values of various solar wind plasma parameters. Recent advances in modeling of high-speed solar wind and coronal mass ejections, combined with the probabilistic forecasting of scintillation, will lead to improved operational space weather forecasting applications. Scintillation forecasting and mitigation techniques need to be developed to avoid potential costly failures of technology-based Global Navigation Satellite Systems in the near future, in particular during the upcoming solar maximum. The Global Navigation Satellite Systems receiver-tracking performance during severe scintillation conditions can be assessed by the analysis of receiver phase-locked-loop jitter. Tracking jitter maps [Sreeja et al. 2011] offers a potentially useful tool to provide users with expected tracking conditions, if based on scintillation predictions as proposed above. Scintillation indices are obtained from L1 GPS data collected with the Canadian High Arctic Ionospheric Network. Combined with high rate amplitude and phase data, they can be used as input to receiver tracking models to develop scintillation mitigation techniques.